Identification of mycolic acid forms using surface-enhanced Raman scattering as a fast detection method for tuberculosis - Perumal J (Dove Medical Press, 2018)
Jayakumar Perumal,1 US Dinishm,1 Anne K Bendt,2 Agne Kazakeviciute,1,3 Chit Yaw Fu,1 Irvine Lian Hao Ong,4 Malini Olivo1 1Laboratory of Bio-optical Imaging, Singapore Bioimaging Consortium, Agency for Science, Technology, and Research (A*STAR), Singapore; 2Singapore Lipidomics Incubator, Life Sciences Institute, National University of Singapore, Singapore; 3Department of Statistical Science, University College London, London, UK; 4Matralix Pte Ltd, Singapore Background: Tuberculosis (TB) is the ninth leading cause of death worldwide and the leading cause from a single infectious agent, based on the WHO Global Tuberculosis Report in 2017. TB causes massive health care burdens in many parts of the world, specifically in the resource constrained developing world. Most deaths from TB could be prevented with cost effective early diagnosis and appropriate treatment.Purpose: Conventional TB detection methods are either too slow as it takes a few weeks for diagnosis or they lack the specificity and accuracy. Thus the objective of this study was to develop a fast and efficient detection for TB using surface enhanced Raman scattering (SERS) technique.Methods: SERS spectra for different forms of mycolic acids (MAs) that are both synthetic origin and actual extracts from the mycobacteria species were obtained by label-free direct detection mode. Similarly, we collected SERS spectra for γ-irradiated whole bacteria (WB). Measurements were done using silver (Ag) coated silicon nanopillar (Ag SNP) as SERS substrate.Results: We report the SERS based detection of MA, which is a biomarker for mycobacteria species including Mycobacterium tuberculosis. For the first time, we also establish the SERS spectral characterization of the three major forms of MA – αMA, methoxy-MA, and keto-MA, in bacterial extracts and also in γ-irradiated WB. We validated our findings by mass spectrometry. SERS detection of these three forms of MA could be useful in differentiating pathogenic and nonpathogenic Mycobacterium spp.Conclusions: We have demonstrated the direct detection of three major forms of MA – αMA, methoxy-MA, and keto-MA, in two different types of MA extracts from MTB bacteria, namely delipidated MA and undelipidated MA and finally in γ-irradiated WB. In the near future, this study could pave the way for a fast and efficient detection method for TB, which is of high clinical significance. Keywords: Mycobacterium tuberculosis, MTB, nontuberculosis mycobacteria, NTM, mycolic acid, MA, SERS, silver-coated silicon nanopillars, Ag SNPs, liquid chromatography mass spectrometry, LC-MS